The Fundamental Right for a Balanced Environment - Bertoldi, Márcia; Massaú, Guilherme (Yuridika, 2022)
This paper reflects on the fundamental duty, extracted from art 225, caput, of the Brazilian Constitution, to protect and defend the environment. It refers to the duty arising from the fundamental right to an ecologically balanced environment. As it is a fundamental right, it defends the existence of a corresponding duty, in this case, a fundamental duty. Such a fundamental duty involves the relationship between present and future generations. The present generation must maintain and protect existing natural resources so the future generation may also enjoy the same natural resources. To reach the proposed objective, this paper adopts a deductive approach, has a qualitative character and uses the bibliographical-documentary procedure for its development. It concludes that the duty provided for in art 225, caput, is not enforceable by itself because it lacks efficacy; however, the right and duty to and with the environment are associated constitutional categories that become effective in return.